Designing and tracking knowledge management metrics - Garcia-Perez, Alexeis; Gheriss, Farah; Bedford, Denise (Working methods for knowledge management, 2019)
Knowledge management metrics are one of the weakest areas of practice in the field. Overwhelmingly, the literature that exists focuses on case studies and incidents of metrics, rather than approaching the concept holistically.Addressing this lack, expert authors Alexeis Garcia-Perez, Farah Gheriss and Denise Bedford come together to supply a fundamental discussion of measurement cultures and philosophy, types of metrics, and how to use metrics to grow an organization. They offer a guide for knowledge management professionals to report on progress against goals and targets in terms that are understandable and comparable to their organizational peers, enabling professionals from across businesses to communicate with metrics and engage in wider discussion about the process of achieving organizational visions.Providing practical guidance for identifying different types of measurements and metrics, as well as methods for defining and collection information about metrics, this is an essential book for knowledge management professionals and researchers on the path to improving metric literacy across their organizations.